Rewriting Fate: Draupadi’s Agency and Narrative Disruption in the Mahabharata’s Dice Game (Pursuits: A Journal of English Studies, 2025)
This paper reexamines the ill-framed dice game in the Mahabharata not as a passive episode of humiliation but as a charged site of political resistance and narrative disruption. While traditionally framed as a ritual of power designed by Shakuni and exploited by the Kauravas, it unveils deeper questions of justice, gender, and moral agency. Draupadi, far from a silent victim, appears as a transformative ethical force that challenges the patriarchal structures and seeks her freedom of choice. Her public questioning of the legality of the game and the silence of the elders becomes a radical act of defiance, troubling the deterministic flow of dharma and shifting the epic’s trajectory from passive fate to active dissent. By invoking agency in a moment of intense ritualized degradation, Draupadi destabilizes the hegemonic masculinity that governs the royal court and reasserts moral consciousness in a collapsing ethical order. Drawing from theoretical frameworks of Giddens and Archer, the paper argues that Draupadi functions as a temporal corporate agent who interrupts narrative linearity, compelling a reevaluation of epic structure and social justice. Her voice reframes the dice game not as a spectacle of defeat, but as the beginning of revolutionary imagination to justify her assertive personality. This article adds knowledge to prevailing scholarship on gender and agency in the Mahabharata by reframing Draupadi’s role in the dice game as an act of political resistance and ethical disruption, rather than passive victimhood.